Hypernuclear cluster states of BΛ12 unveiled through neural network-driven microscopic calculation - Jiaqi Tian; Mengjiao Lyu; Zheng Cheng; Masahiro Isaka; Akinobu Doté; Takayuki Myo; Hisashi Horiuchi; Hiroki Takemoto; Niu Wan; Qing Zhao (Physics Letters B)
We investigate the hypernuclear cluster states of BΛ12 using a neural-network-driven microscopic model. We extend the Control Neural Networks (Ctrl.NN) method and systematically calculate the positive-parity spectrum of BΛ12. By incorporating sd-shell excitations and parity-coupling effects into the BΛ12 hypernuclear system, we reveal structural changes, including clustering effects and new configurations such as isosceles-triangle and α-t-α linear-chain structures. Furthermore, by comparing with experimental data, we identify that many peaks (#6 and #8) can be interpreted as pΛ dominant states, which is consistent with shell-model predictions. Notably, based on our analysis of the excited states of BΛ12, we propose possible candidates for previously unexplained or controversial experimental peaks.